Quality of Source Water and Drinking Water in Urban Areas of Myanmar - Hiroshi Sakai; Yatsuka Kataoka; Kensuke Fukushi (The Scientific World Journal, 2013)
Myanmar is one of the least developed countries in the world, and very little information is available regarding the nation’s water quality. This report gives an overview of the current situation in the country, presenting the results of various water-quality assessments in urban areas of Myanmar. River, dam, lake, and well water sources were examined and found to be of generally good quality. Both As and F- were present in relatively high concentrations and must be removed before deep wells are used. Heterotrophic plate counts in drinking water were highest in public pots, followed by nonpiped tap water, piped tap water, and bottled water. Measures need to be taken to improve low-quality water in pots and nonpiped tap waters.